A sudden shedding: azathioprine induced anagen effluvium - Mogiligari, Sreeja; Parimi , Vijaya P. (International Journal of Research in Dermatology, 2025)
Azathioprine is commonly used as immunosuppressive therapy for various autoimmune diseases including Takayasu arteritis. Myelosuppression is a recognized side effect of azathioprine, often requiring dose reduction. However, severe alopecia is rarely encountered. Here, a case of azathioprine-induced anagen effluvium and leucopenia that occurred in a 26-year-old woman with Takayasu arteritis who developed sudden diffuse non-scarring alopecia and leucopenia within three weeks of starting azathioprine therapy.